(untitled) (The Research of Medical Science Review, 2025)
Background: Over the years, the incidence of interstitial lung disease which is associated with work environments, OILD has risen with continuous exposure to deleterious agents such as asbestos, coal dust as well as silica dust. Elimination and management of OILD is most effective when diagnosis is made as early as possible. This has been achieved with the application of high-resolution computed tomography. HRCT OILD has emerged as the most preferred tool in early OILD detection as lung changes may not always be present on x-ray chest films. Objective: The purpose of this study is to determine the effectiveness of HRCTs in diagnosing OILD in workers from different industries exposed to hazardous elements of the workplace. The study also seeks to correlate the level of occupational exposure and the other forms of lung pathology that can be classified as disease, which can be both malignant or benign. Method: This was a cross-sectional study conducted on 120 participants across different industries: Bricks Factory (46.7%), Textile Industry (26.7%), Cement Industry (9.2%), and Sugar Mills (17.5%). Participants were subjected to lung CT scan HRCT in the detection of lung changes. Correlation analysis revealed a link between occupational history and lung disease diagnoses, which ranged from benign, malignant to nil conditions. The relationship between occupation and lung diseases was studied using Pearson Chi-Square test. Result: The findings revealed that workers at the Bricks Factory had the highest levels of lung involvement, particularly the Right and Left Anterior lung segments. Employees in the Textile Industry had less affected lung segments, mostly in the Right Anterior portion. The Cement Industry had the least amount of lung involvement, which was primarily in the Bilateral Anterior segments. In contrast, the Sugar Mill Workers had a moderate range of lung abnormalities. The Bricks Factory group also had the largest percentage of malignant diagnoses (74.5% of all malignant cases) while the Textile Industry had mostly benign diagnoses. A very strong association between the diagnosis and occupational exposure was observed (p < 0.001, Pearson Chi-Square = 29.428).